2015
DOI: 10.1177/1477370815608881
|View full text |Cite
|
Sign up to set email alerts
|

How is parenting related to adolescent delinquency? A between- and within-person analysis of the mediating role of self-control, delinquent attitudes, peer delinquency, and time spent in criminogenic settings

Abstract: We examined how parenting is directly and indirectly associated with adolescent delinquency. We derived four possible mechanisms from major criminological theories and examined their relative contribution to explaining the relationship between parenting and delinquency: selfcontrol theory (that is, self-control), differential association theory (that is, delinquent attitudes and peer delinquency), and routine activity theory (that is, time spent in criminogenic settings). In addition, we examined how changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 57 publications
3
67
1
1
Order By: Relevance
“…These results offer little support for the routine activity perspective. However, results of a previous study have shown that time spent in criminogenic settings was relatively unstable over time (Janssen et al 2016). The amount of time spent in criminogenic settings at T1 was not strongly related to the amount spent in criminogenic settings at T2.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…These results offer little support for the routine activity perspective. However, results of a previous study have shown that time spent in criminogenic settings was relatively unstable over time (Janssen et al 2016). The amount of time spent in criminogenic settings at T1 was not strongly related to the amount spent in criminogenic settings at T2.…”
Section: Discussionmentioning
confidence: 75%
“…In addition to the mechanisms derived from self-control theory and differential association theory, we examined the unique contribution of a relatively new construct to explain the link between parenting and delinquency: time spent in criminogenic settings (Janssen et al 2016). According to the routine activity perspective (Cohen and Felson 1979) higher levels of involvement in delinquency among boys might be the results of more exposure to criminogenic settings.…”
Section: Sex Differences In Indirect Pathways From Parenting To Delinmentioning
confidence: 99%
“…Bu bağlamda sapkın arkadaşların riskli davranışları etkilemede oynadıkları rolün bilinmesinin riskli davranışları önleme ve bu davranışlara müdahale çalışmalarına katkı sağlayacağı düşünülmektedir. Son yıllarda yapılan araştırmalar aile takibi (Goldstein, Davis-Kean ve Eccles, 2005;Kim ve Neff, 2010), ebeveynlik stili (Janssen, Eichelsheim, Dekovic ve Bruinsma, 2015), örselenme yaşantısı (Negriff vd., 2015), depresyon (Pesola vd., 2015) ve akran zorbalığı Zhu vd., 2016) ile riskli davranışlar arasındaki ilişkilerde sapkın arkadaşların aracılık rolünü incelemişlerdir. Bu çalışmanın önceki araştırmalardan farklı olarak amacı çocukluk çağı örselenme yaşantısı, akran zorbalığı ve psikolojik sağlamlığın riskli davranışlarla ilişkisinde sapkın arkadaşların aracılık etkisini açıklayan bütüncül bir model geliştirmektir (bkz.…”
Section: Introductionunclassified
“…Building on previous work by Janssen and colleagues (2014;2016a;2016b;, we have attempted to further explore how different aspects of parental monitoring are related to adolescent criminogenic exposure. Knowledge about why some adolescents are at increased risk of being exposed to criminogenic settings is important in order to reduce the risk of delinquent activity among adolescents (Janssen et al, 2016a;Wikström et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Building on previous work by Janssen and colleagues (2014;2016a;2016b;, we will examine the relationship between changes in parental monitoring and adolescents criminogenic exposure over time. The present study will add to the findings by Janssen and colleagues by examining two monitoring-related measures that have not previously been studied within this area.…”
Section: Present Studymentioning
confidence: 99%